Wild hunger : an heirs of Chicagoland novel - Neill, Chloe (An heirs of Chicagoland novel, 2018)
"In the first thrilling installment of Chloe Neill's spinoff to the New York Times bestselling Chicagoland Vampires series, a new vampire will find out just how deep blood ties run. As the only vampire child ever born, some believed Elisa Sullivan had all the luck. But the magic that helped bring her into the world left her with a dark secret. Shifter Connor Keene, the only son of North American Central Pack Apex Gabriel Keene, is the only one she trusts with it. But she's a vampire and the daughter of a Master and a Sentinel, and he's prince of the Pack and its future king. When the assassination of a diplomat brings old feuds to the fore again, Elisa and Connor must choose between love and family, between honor and obligation, before Chicago disappears forever"--